Prevalence of Abnormal Glucose Challenge Test and Oral Glucose Tolerance Test in Pregnancy - Shrestha, Buddhi Kumar; Bhandari, Shanti (Journal of College of Medical Sciences-Nepal, 2023)
Introduction Gestational Diabetes is one of the most prevalent endocrine disorders during pregnancy; associated with adverse maternal and fetal outcome. So, screening is mandatory for timely diagnosis and management. The main objective of this research is to find the prevalence of abnormal glucose challenge test and oral glucose tolerance test in pregnancy. Methods A cross-sectional study was conducted among 480 antenatal women of 24-28 weeks gestation at College of Medical Science-Teaching Hospital Bharatpur, Nepal from Jan-Dec 2020 after ethical approval from COMS-IRC. Results Gestational diabetes mellitus was most common in women of age group 20-30 years (62.06%). Higher percent of women with gestational diabetes were Multigravida (75.86%), high body mass index (p-value: 0.01). Fifty eight percent women with gestational diabetes had statistically significant family history of diabetes in first degree relatives (p-value 0.036). In our study, prevalence of impaired glucose challenge test was 60 (12.5%) and that of gestational diabetes mellitus was 29 (6.04%). Conclusions The prevalence of gestational diabetes mellitus is high with multiparity, family history of diabetes and obesity. The test is easy, cheap, feasible and patient friendly method for screening gestational diabetes mellitus.